Associations of early-life adversities with inflammatory profiles in midlife: evidence from two cohorts in the UK and USA. (November 2018) - Pinto Pereira, Snehal M; Merkin, Sharon Stein; Seeman, Teresa; Power, Chris
Abstract: Background: Inflammation is one hypothesised mechanism by which early-life adversities (ELAs) impact adult health. In cohorts from the UK and USA, we aimed to establish associations between ELAs and adult inflammation, and whether adult adiposity or socioeconomic disadvantage are key intermediaries. Methods: The 1958 birth cohort includes all infants born during 1 week in March, 1958, across Britain; biomedical data were collected at 45 years. Midlife in the United States (MIDUS) is a national English-speaking sample of 25–75 year olds, initiated in 1994–95; 9–10 years later, a biomarker project was undertaken. In 7661 participants in the 1958 birth cohort and 1255 participants in the MIDUS cohort, linear regression was used to examine associations between ELAs (neglect, emotional neglect, physical, psychological, sexual abuse, and childhood disadvantage, recalled or prospectively recorded), adult adiposity (body-mass index, waist-to-hip ratio), socioeconomic disadvantage, and inflammatory markers (C-reactive protein [CRP], fibrinogen, and [MIDUS only] interleukin 6). Findings: ELAs varied from 1·6% (sexual abuse, 1958 birth cohort, n=123) to 14·3% (socioeconomic disadvantage, MIDUS, n=178). Across cohorts, associations were consistent for physical abuse (eg, 16·3% [95% CI 3·01–29·7, p=0·02] and 17·0% [16·4–50·3, p=0·30] higher CRP in the 1958 birth cohort and MIDUS, respectively). There were several associations between ELAs and adiposity and, between adiposity and inflammatory markers. ELA–inflammatory marker associations attenuated after accounting for adiposity. For example, physical abuse (1958 birth cohort) and sexual abuse (MIDUS, non-white participants) associations were abolished. Some associations attenuated after adjustment for socioeconomic disadvantage—eg, in the 1958 birth cohort, neglect–CRP associations reduced from 23·2% (13·7–32·6, p<0·0001) to 17·7% (8·18–27·2, p<0·0001). Across cohorts, associations were absent for psychological abuse or emotional neglect and inconsistent for childhood socioeconomic disadvantage. Interpretation: Study strengths include use of two populations with potentially differing confounding structures (eg, the UK's universal welfare vs the USA's private care) and, wherever possible, we standardised definitions and approaches, overcoming previously identified limitations. Some ELAs were recorded retrospectively, possibly affecting recall, and availability of exposures sometimes differed between studies. Although causality remains challenging to establish, we found that specific ELAs were associated with adult inflammation and that adiposity is a likely intermediary factor. Weight reduction and obesity prevention might offset pro-inflammatory related disease among people who experienced specific ELAs. The findings emphasise the need to consider ELAs separately in relation to long-term outcomes such as inflammatory status. Funding: Research reported in this abstract was supported by theUS National Institute on Aging of the National Institutes of Health (NIH) (award no U24AG047867 ) and theUK Economic and Social Research Council and the Biotechnology and Biological Sciences Research Council (award no ES/M00919X/1 .